Assembly and analysis of the mitochondrial genome of Prunella vulgaris - Sun, Zhihao; Wu, Ya; Fan, Pengyu; Guo, Dengli; Zhang, Sanyin; Song, Chi (Frontiers in Plant Science, 2023)
Prunella vulgaris (Lamiaceae) is widely distributed in Eurasia. Former studies have demonstrated that P. vulgaris has a wide range of pharmacological effects. Nevertheless, no complete P. vulgaris mitochondrial genome has been reported, which limits further understanding of the biology of P. vulgaris. Here, we assembled the first complete mitochondrial genome of P. vulgaris using a hybrid assembly strategy based on sequencing data from both Nanopore and Illumina platforms. Then, the mitochondrial genome of P. vulgaris was analyzed comprehensively in terms of gene content, codon preference, intercellular gene transfer, phylogeny, and RNA editing. The mitochondrial genome of P. vulgaris has two circular structures. It has a total length of 297, 777 bp, a GC content of 43.92%, and 29 unique protein-coding genes (PCGs). There are 76 simple sequence repeats (SSRs) in the mitochondrial genome, of which tetrameric accounts for a large percentage (43.4%). A comparative analysis between the mitochondrial and chloroplast genomes revealed that 36 homologous fragments exist in them, with a total length of 28, 895 bp. The phylogenetic analysis showed that P. vulgaris belongs to the Lamiales family Lamiaceae and P. vulgaris is closely related to Salvia miltiorrhiza. In addition, the mitochondrial genome sequences of seven species of Lamiaceae are unconservative in their alignments and undergo frequent genome reorganization. This work reports for the first time the complete mitochondrial genome of P. vulgaris, which provides useful genetic information for further Prunella studies.